Il coraggio delle immagini - Fagioli, Massimo (Il sogno della farfalla, 2025)
The aim of this article is to present the writings originally published in 1995, as part of the catalogue for the exhibition “Il coraggio delle immagini”. In these texts, Fagioli delves into the conceptual and experiential dimensions of architectural creation through the lens of his Human Birth Theory, conceiving it as an act in which internal images, beauty, and material reality intersect within a dynamic process of transformation. Moving beyond the dichotomy of utility versus aesthetics, the author explores the “courage of images” as a constructive and transformative force capable of redefining the relationship between human beings, nature, and the built environment. The discussion unfolds across multiple themes: the materialization of inner images into architectural form; the interplay between conscious and unconscious processes in design; and the unique position of architecture among the arts. Drawing parallels with the visual arts, the text emphasizes the architect’s special responsibility to mediate between imagination, material constraints, and ethical considerations. Ultimately, it underscores the importance of the architect’s ability to detach from and “forget” their creation, allowing it to exist independently.